왕겨숯을 이용하여 제조한 보드의 물성 - 황정우; Jung-woo Hwang; 오승원; Seung-won Oh (목재공학, 2017)
본 연구는 쌀의 도정과정에서 발생되는 농업부산물인 왕겨를 탄화시켜 만든 왕겨숯을 톱밥과 혼합하여 밀도별, 수지첨가율별 및 톱밥첨가율별로 보드를 제조하고 기초물성을 측정하여 보드 재료로서의 이용가능성을 검토하였다. 수분흡수율은 수지첨가량 25%일 때 80.09%로 가장 낮은 값을 나타냈고, 밀도가 증가하고 톱밥첨가량이 감소할 때 수분흡수율이 감소하는 경향을 나타냈다. 또한 측정된 두께팽윤율은 KSF 3104 파티클보드의 품질규정에 만족시키고 있어 치수안정성 부분에서 건축내장재로 활용가능성이 확인되었다. 박리강도는 수지첨가량 25%일 때 0.24 N/mm 2 으로 KSF 3104 파티클보드의 품질기준을 만족시켰지만, 나머지 조건에서는 현저하게 낮은 값을 나타내 조건을 충족시키지 못하였다. 밀도, 수지첨가율, 톱밥첨가율이 증가할수록 경도도 증가하는 경향을 나타냈다. This study was investigated on the properties of board made from carbonized rice husk differed in density of board, resin addition ratio and sawdust addition ratio. Water absorption is showed the lowest value to 80.09% when the resin addition ratio of 25%, as the density increased and sawdust addition ratio decreased, the water absorption was decreased. The measured thickness swelling satisfied with the quality standards of KS F 3104, so the feasibility of building interior has been confirmed in the dimensional stability. In case of resin addition ratio of 25%, the internal bond strength was satisfied quality standards of KS F 3104 to 0.244 N/mm 2 . With increasing the density, resin and sawdust addition ratio, brinell hardness increased.